A retrospective comparative study to evaluate the efficacy and safety of mifepristone with misoprostol over misoprostol alone in induction in labor - Sharma, Reena; Sharma, B. R.; Dogra, Poojan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to compare the improvement in pre-induction Bishop’s score, proportion of patients going in labor and induction–delivery interval after using the Misoprostol versus Mifepristone and Misoprostol as cervical ripening and labor inducing agent. Methods: It is retrospective comparative study conducted on 110 women. Women were randomized in group A and in group B of 55 patients in each group. Group A received tab Mifepristone 200 mg orally on day 1 followed by Misoprostol 25 ug after 48 hours and continued 6 hourly till maximum four tablets and group B patients received tablet Misoprostol 25ug and continued 25ug 6hrly maximum 4 doses. Women observed for improvement in Bishop‟s score, induction-delivery interval and requirement of subsequent doses of Misoprostol. Results: Present study concluded that tablet Mifepristone is an efficient cervical ripening and inducing agent of labor as pre-induction Bishop’s score was improved. 36.4%patients went into labor only with tablet Mifepristone. The mean induction-delivery interval was,19±12.2hrs in Group 1 as compare to 13.1±13.0 hrs in Group 2. Mean Bishop’s score observed in Group 1 were 2.5±1.78 and 1.67±1.25 in Group 2. It was observed that there was significant improvement in the Bishop’s score after giving Mifepristone to the patients; mean Bishop’s 24hrs after mifepristone were 4.03±1.80. Repeated dose of Misoprostol required in Group 1 was observed to be higher than group 2 as shown in table 8. Mean misoprostol doses required in group 1 was 2.56±1.15 as compared to 1.71±1.58 in group 2. Conclusions: Mifepristone with Misoprostol reduce the induction delivery interval and more potent in combination for induction of labour as compared to Misoprostol alone.